What do we know about pathological mechanism and pattern of lung injury related to SARS-CoV-2 Omicron variant? - Roberto Scendoni; Mariano Cingolani (BMC, 2023)
Abstract Pulmonary damage in SARS-CoV-2 is characterized pathologically by diffuse alveolar damage (DAD) and thrombosis. In addition, nosocomial bacterial superinfections and ventilator-induced lung injury (VILI) are likely to occur. The SARS-CoV-2 Omicron variant have manifested itself as a more diffusive virus which mainly affects the upper airways, such as the nose and pharynx. The mechanism leading to a lung injury with a complex clinical course for the Omicron SARS-CoV-2 variant remains unclear. A key question is whether the organ damage is due to direct organ targeting of the virus or downstream effects such as an altered immune response. An immune escape process of Omicron variant is being studied, which could lead to prolonged viral shedding and increase hospitalization times in patients with comorbidities, with an increased risk of pulmonary co-infections/superinfections and organ damage. This brief commentary reports the current knowledge on the Omicron variant and provides some useful suggestions to the scientific community.